A MIS 15-MIS 12 record of environmental changes and Lower Palaeolithic occupation from Valle Giumentina, central Italy. (1st November 2016) - Villa, Valentina; Pereira, Alison; Chaussé, Christine; Nomade, Sébastien; Giaccio, Biagio; Limondin-Lozouet, Nicole; Fusco, Fabio; Regattieri, Eleonora; Degeai, Jean-Philippe; Robert, Vincent; Kuzucuoglu, Catherine; Boschian, Giovanni; et al.
Abstract: An integrated geological study, including sedimentology, stable isotope analysis (δ 18 O, δ 13 C), geochemistry, micromorphology, biomarker analysis, 40 Ar/ 39 Ar geochronology and tephrochronology, was undertaken on the Quaternary infill of the Valle Giumentina basin in Central Italy, which also includes an outstanding archaeological succession, composed of nine human occupation levels ascribed to the Lower and Middle Palaeolithic. 40 Ar/ 39 Ar dating, and other palaeoenvironmental and tephrochronological data, constrain the sedimentary history of the whole succession to the MIS 15-MIS 12 interval, between 618 ± 13 ka and 456 ± 2 ka. Palaeoenvironmental proxies suggest that over this time interval of about 150 ka, sedimentary and pedogenic processes were mainly influenced by climatic changes, in particular by the pulsing of local mountain glaciers of the Majella massif. Specifically, the Valle Giumentina succession records glacio-fluvial and lacustrine sedimentation during the colder glacial periods and pedogenesis and/or alluvial sedimentation during the warmer interglacial and/or interstadial periods. During this interval, tectonics played a negligible role as a driving factor of local morphogenesis and sedimentation, whereas the general regional uplift experienced in the Middle Pleistocene led to capture of the basin and its definitive extinction after MIS 12. These data substantially improve previous knowledge of the chronology and sedimentary evolution of the succession, providing for the first time, a well constrained chronological and palaeoenvironmental framework for the archaeological and human palaeoecological record of Valle Giumentina. Highlights: Valle Giumentina is a key site for the European Lower Palaeolithic. A multidisciplinary study was performed on the infill of the Valle Giumentina basin. The Quaternary environmental evolution of the basin was reconstructed. The sedimentary sequence spans the MIS 15-MIS 12 time interval. The site is 200 ka years older than previously estimated.